Gender-Based Violence in Intimate Relationships and Stereotypes in the Justice System: Lessons from the CEDAW Committee - Cardoso Onofre de Alencar, Emanuela (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
This paper studies gender stereotyping in the justice system in cases of intimate violence. First, it examines what are stereotypes, what are their main effects and points out some of the most frequent stereotypes in cases of intimate violence. Then it analyses the contribution of the CEDAW Committee on this subject. The Committee has a ground-breaking work in the linkages between stereotyping, discrimination and gender-based violence, and in the last years has underlined how gender stereotyping in the justice system, especially in cases of intimate violence, undermines human rights and discriminate. Its work offers international standards to address this kind of violence, leads legal development on this subject, and gives arguments to take seriously stereotyping in the justice system.